2020
DOI: 10.1155/2020/8851997
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Anemia and Its Associated Factors among Pregnant Women Attending Antenatal Care at Najo General Hospital, Northwest Ethiopia

Abstract: Anemia is one of the major causes of morbidity for pregnant women in resource-limited regions. Yet robust research-based evidence on this vital public health problem in remote areas where the problem could be massive is quite limited in Ethiopia, one of the developing countries. Thus, this study is aimed to assess the magnitude of anemia and its associated risk factors among pregnant women attending one of the health facilities in Ethiopia. A facility-based cross-sectional study design was employed in 2019. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
(24 reference statements)
3
10
0
Order By: Relevance
“…The current results both showed that most respondents have at-risk parity and indicated that parity does not significantly affect anemia in pregnant women, as the proportion of anemia among pregnant women with at-risk and no-risk parity was the same. This is in line with research conducted by Gari, Tsegaye, & Ketema (2020), which showed that parity did not have a significant association with anemia.…”
Section: Paritysupporting
confidence: 92%
“…The current results both showed that most respondents have at-risk parity and indicated that parity does not significantly affect anemia in pregnant women, as the proportion of anemia among pregnant women with at-risk and no-risk parity was the same. This is in line with research conducted by Gari, Tsegaye, & Ketema (2020), which showed that parity did not have a significant association with anemia.…”
Section: Paritysupporting
confidence: 92%
“…The possible explanation for anaemia related death during the postpartum period relates to women's circulatory decomposition, which is manifested by increased cardiac output and decreased ability to blood loss, which ultimately results in shock and death [97]. On the other hand, the risk factors of anaemia such as low dietary intake of iron, intestinal or blood parasite infection, and chorine illness [98,99], could be handled during ANC visit by supplementation of iron, folic acid, and deworming.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia in pregnant women can be caused by parasitic infestation, socio-demographic status, economic status, dietary practice, obstetric factors, reproductive health, and other health-related factors [ 5 ]. More than 115,000 maternal deaths and 591,000 prenatal deaths are caused by anemia disease in the world per year [ 6 ]. According to the World Health Organization (WHO, 1993–2005) report, anemia affects 41.8% of pregnant women worldwide, with Africa having the highest prevalence (57.1%) [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the women who live in the rural areas of Ethiopia have been affected by this disease due to different factors including nutrition, parasites, socio-demographic, obstetric, reproductive characteristics, and the like [ 10 ]. According to WHO guidelines, the minimum acceptable hemoglobin level during pregnancy is 11 g/dl, during the first half, 10.5 g/dl, during the second half, and 12 g/dl for lactating women [ 6 , 10 , 11 ]. To understand and predict the level of anemia among pregnant women in the case of Ethiopia, several types of research have been conducted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation